Climate and health in Asia: a scoping review of vulnerability and community adaptation - Dharmayanti, Ika; Azhar, Khadijah; Purwana, Rachmadhi; Tjandrarini, Dwi Hapsari; Soesilo, Tri Edhi Budhi (The Journal of Infection in Developing Countries, 2026)
Introduction: Climate change intensifies environmental risks across Asia, disproportionately affecting vulnerable populations and exacerbating health disparities. However, evidence on community adaptation strategies and the integration of health dimensions into adaptation policies remains fragmented. This scoping review aimed to map climate-sensitive health risks, evaluate the equity and effectiveness of community adaptation measures, and examine theoretical frameworks for vulnerability assessments across Asia. Methodology: Guided by the PRISMA-ScR checklist, this scoping review analyzed 21 peer-reviewed studies on climate-health interactions and adaptation strategies in Asia published between 2008 and 2024. Data were systematically charted and synthesized thematically. Results: Five cross-cutting themes emerged: physical and socioeconomic exposure, gender-related vulnerability, community-based and informal adaptation, climate-related health impacts, and institutional and policy gaps. Adaptation strategies rely heavily on community-led practices with limited attention to gender and health in national plans. The review also highlights challenges to equity in community adaptation and critiques existing vulnerability frameworks. This review underscores the need for justice-oriented, integrated approaches to climate and health. Conclusions: This review underscores the importance of integrating community knowledge and gender-sensitive approaches into climate–health frameworks. Strengthening health systems and formalizing local adaptation practices are essential for reducing inequities. Future research should adopt longitudinal and interdisciplinary perspectives to capture long-term health outcomes and policy implementation barriers in rapidly urbanizing environments.